Pengaruh Return on Asset, Return on Equity dan Earning Per Share Terhadap Harga Saham pada Perusahaan Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Wirda Lilia; A Surya Raj; Jesica Jesica; Faren Goh (Universitas Batanghari Jambi, 2021)
The research carried out in the Consumer Goods Sector Company iaims ito ianalyze ithe iEffects iof iReturn ion iAssets, iReturn ion iEquity iand iEarning iPer iShare ion iShare iPrices iin iConsumer iGoods iSector iCompanies iListed ion ithe iIndonesia iStock iExchange.iThe iresearch ipopulation iis i41 icompanies iand ionly i21 icompanies ithat imeet ithe icriteria ias ia isample iusing ipurposive isampling itechnique.iThe iresearch imethod iuses imultiple ilinear iregressionianalysis iwith ithe iclassic iassumption itest.iThe iresults iof ithe iF itest iare iobtained ithat iReturn ion iAssets, iReturn ion iEquity iand iEarning iPer iShare iaffect ithe iStock iPrices iof iConsumers' iGoods iSector iCompanies iListed ion ithe iIndonesia iStock iExchange. In the t test the variable Return on Assets idoes inot iaffect ithe istock iprice iof iconsumer igoods icompanies ilisted ion ithe iIndonesia iStock iExchange.iReturn ion iEquity iaffects istock iprices ion iconsumer igoods icompanies ilisted ion ithe iIndonesia iStock iExchange.iEarning iPer iShare iaffects ithe iprice iof ishares iin iconsumer igoods icompanies ilisted ion ithe iIndonesia iStock iExchange.